Evaluating OSH Work Environment Implementation at PLN Offices: Impact of Safety Climate and Behavior - Annisa Azzahra; Ahlul Zikri; Taufiq Ihsan (Preventif : Jurnal Kesehatan Masyarakat, 2026)
This study evaluates the implementation of Occupational Safety and Health (OSH) practices at PT. PLN (Persero) UP3 Padang. The electricity sector faces significant OSH challenges, and while research has explored OSH in various settings, a gap remains in the evaluation of OSH practices within Indonesian office environments. This study aims to address this gap by evaluating OSH work environment implementation at PT. PLN (Persero) UP3 Padang based on the Indonesian Ministry of Manpower Regulation/ Pemenaker No. 5 of 2018. The research employs a primarily quantitative approach, utilizing a descriptive survey design. Data, gathered through questionnaires, assessed OSH implementation (based on Permenaker No. 5 of 2018), safety climate, and employee safety behavior. The results indicate that PT. PLN (Persero) UP3 Padang has demonstrated a strong commitment to OSH, achieving a generally high level of compliance with Permenaker No. 5 of 2018. Employees reported a positive safety climate, with high average scores for management commitment (approximately 3.55). Employee adherence to safe work practices was also high, although hazard reporting behavior received a lower average score of 3.56. Furthermore, the reporting and communication culture dimension within the safety climate was the lowest at 3.28. A strong positive correlation was found between safety climate and OSH implementation (ρ = 0.7218; p < 0.001). The study concludes that while OSH implementation is generally effective, there are areas for improvement, including controls for specific hazards and hazard reporting. Continuous improvement and targeted interventions are crucial for enhancing OSH performance within the organization and similar office settings.